ADRENAL HISTOPLASMOSIS AND BILATERAL ADRENAL ENLARGEMENT: A CASE SERIES IN PPUKM - K, Waye Hann; AW, Norasyikin; K, Nor Azmi (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Histoplasmosis is an opportunistic systemic mycosis caused by the endemic dimorphic fungi H. capsulatum. Adrenal histoplasmosis can occur as a sequela of disseminated histoplasmosis especially in immunosuppressed individuals, presenting as unilateral or bilateral adrenal enlargement with constitutional symptoms and/or adrenal insufficiency. Often these patients are initially investigated as malignancies with secondary adrenal metastases before eventually having their diagnosis established by histopathological examination (HPE) of the adrenal tissues. METHODOLOGY This is a retrospective study of 4 cases presented as bilateral adrenal masses and later diagnosed with adrenal histoplasmosis by HPE in Pusat Perubatan Universiti Kebangsaan Malaysia from 2008-2018. RESULTS Four patients were diagnosed with adrenal histoplasmosis and all of them were Malay men (mean age 68.8 years). Two were retired army officers, while 1 was a retired agricultural officer. One patient had no occupational exposure but has exposure to bat guano in his residence. One had diabetes, while another had chronic kidney disease due to long-standing hypertension. None of them were HIV positive. The most common presentation was constitutional symptoms (75%) while two presented as Addisonian crisis. All of them had bilateral enlarged adrenals on abdominal CT with the largest dimension ranging from 3.0-7.3 cm. All of them were diagnosed on HPE by the presence of small ovoid yeast-like organisms identified in Periodic-Acid-Schiff (PAS) and Gomori Methenamine-Silver (GMS) stains in the adrenal necrotic tissue with granulomatous inflammation. Three of them received anti-fungal treatment for at least 1-year duration but 1 had residual primary adrenal insufficiency requiring steroid replacement. CONCLUSION The diagnosis of adrenal histoplasmosis should be ruled out in all patients with bilateral adrenal enlargement by HPE as the prognosis is good with early treatment. However, these patients will require life-long corticosteroid replacement as the adrenal insufficiency did not improve despite completing the treatment.